Development of Problem-Based Learning Mathematical Module with STEM Approach to Improve Problem-Solving Ability and Self Efficacy (Unnes Journal of Mathematics Education, 2023)
The aim of this research was to produce problem-based learning mathematical modules with STEM approach with a valid, practical and effective in improving problem-solving ability and self efficacy. This study used a Research and Development (RnD) with a 4-D development model. The 4-D development process stage consists of Define, Design, Develop, and Disseminate. This research did not reach the disseminate stage due to time constraints. Based on the results of the research, it was found that the problem-based learning mathematical modules with STEM approach that was developed met the criteria, namely, (1) validity with a percentage of 88% with very valid criteria, (2) practicality with a percentage of 91.5% with very strong criteria. practical, (3) effective in increasing problem-solving ability with an n-gain result of 0.64 with medium criteria, (4) effective in increasing self-efficacy with an n-gain result of 0.575 with medium criteria.